The White Paper - An Analysis
1944-03 1944 1940s 12 pages 2 advisory committees representative of the local medical profession which should be at liberty to publish their findings. These administrative changes should be regarded as foundation changes to be agreed before other changes are initiated. PRINCIPLE K. All branches of medical practice should be regarded as a single service, and it is undesirable that a detailed scheme for general practitioners should be framed and put into operation without corresponding arrangements for other branches of practice. (Interim Proposals) PRINCIPLE L. Pending the consideration and completion of the foundation administrative changes mentioned in Principle J above, as a step towards the satisfaction of Assumption B there should be extension of National Health Insurance to include dependants of insured persons and others of like economic status and to cover consultant and specialist services and laboratory and hospital facilities as well as general practitioner service. The service should be improved from time to time as recommended by the profession. Those persons with incomes above an agreed limit could, if Parliament decided to make the service available to every member of the community, be permitted to become voluntary contributors to the extended service. A reconstruction of insurance committees would be necessary. PRINCIPLE M. There should be initiated, by arrangement and agreement between the Government and the profession organized experiments in the methods of practice, such as group practice, including health centres of different kinds, which should extend to general practitioner hospital units attached to general hospitals. Future developments in group practice should depend upon the results of such clinical and administrative experimentation. SUMMARY OF THE WHITE PAPER (reproduced from the abridged edition) 1. Scope of the new Service. (a) A National Health Service will be established. This service will be available to every citizen in England, Scotland and Wales. (b) There will be nothing to prevent those who prefer to make private arrangements for medical attention from doing so. But, for all who wish to use the service it will provide a complete range of personal health care — general and specialist, at home, in the hospital and elsewhere. (c) The service will be free, apart from possible charges for certain appliances. (Questions of disability benefits will be dealt with in later proposals on social insurance.) 2. Structure of the Service. (a) Central. (i) Central responsibility to Parliament and the people will be with the Minister of Health and the Secretary of State for Scotland. (ii) At the side of the Minister there will be a professional and expert advisory body to be called the Central Health Services Council. The Council will be a statutory body and its function will be to provide professional guidance on technical aspects of the Health Service. There will be a similar body in Scotland. (b) Local. (i) Local responsibility will be based on the county and county borough councils, which are the major local government authorities now. They will administer the new service partly in their present separate capacities over their present areas, partly — as the needs of the service require — by combined action in joint boards over larger areas. (ii) Areas suitable for hospital organisation will be designated by the Minister after consultation with local interests. (iii) The county and county borough councils in each area will combine to form a joint authority to administer the hospital, consultant and allied services ; in the few cases where the area coincides with an existing county area the authority will be the county council of that area. (iv) At the side of each new joint authority there will be a consultative body — professional and expert— to be called the Local Health Services Council. (v) Each joint authority will also prepare — in consultation with the Local Health Services Council — and submit for the Minister's approval an "area plan" for securing a comprehensive Health Service of all kinds in its area. (vi) County and county borough councils combining for these duties of the new joint authority will also severally be responsible for the local clinic and other services in accordance with the area plan. Responsibility for child welfare will be specially assigned in whatever way child education is assigned under the current Education Bill. 3. Hospital and consultant Services. (a) It will be the duty of the joint authorities themselves to secure a complete hospital and consultant service for their area — including sanatoria, isolation, mental health services, and ambulance and ancillary services in accordance with the approved area plan. (b) The joint authorities will do this both by direct provision and by contractual arrangements with voluntary hospitals (or with other joint authorities) as the approved area plan may indicate. (c) The powers of present local authorities in respect of these services and the ownership of their hospitals will pass to the joint authority. 21/570